Auditory Risk Factors at Birth and Language Development at 2 Years of Age: A Longitudinal Analysis - Yaser Ramirez PhD; Yuleidys Castillo BSc; Shuyeng Acea MSc; Linda S. Pagani PhD (SAGE Publishing, 2024)
Aim . To analyze the relationship between auditory risk factors at birth and subsequent language development in toddlerhood. Methods . Participants are 136 children from a longitudinal birth cohort follow-up at age 2 years. They were divided into 2 groups: One comprising 105 children without hearing risk factors at birth and another comprising 31 children with auditory risk factors at birth but normal hearing. Results . In children with and without risk factors, the combination of socio-emotional, socio-economic, and auditory risk factors at birth significantly predicted language development at age 2 years. Family socio-economic status had a significant impact on overall child development, even after controlling for socio-emotional development and the presence of risk factors. Conclusions . The study was conducted in an upper-middle income country with a socialized health care system. It underscores the importance of a holistic approach to early childhood language development, taking into account biological, socioeconomic, and emotional factors.